Scholars in exile : the Ukrainian intellectual world in interwar Czechoslovakia - Zavorotna, Nadia, 1969- (University of Toronto Press, 2020)
"Throughout the 1920's and 30's Prague was the intellectual center of Ukrainian emigres in Europe, not least because of significant financial support from the Czech government and its first president, Tomas Gerrigue Masaryk for emigre students and intellectuals."--